Organic Waste Processing in Efforts to Reduce Waste Accumulation: Social and Economic Impacts - Kusuma Dewi, Stevani Eka Putri; Muhammad Irsyad Maulana; Darianto; Sri Yaumi; Ma'rufatur Rodhiyah (Edumedia Solution, 2026)
Organic waste management at SMP Negeri 1 Glagah faces challenges due to sanitation issues, limited facilities, and low environmental awareness. Waste from school activities that has not been managed optimally has led to a significant accumulation of waste, causing environmental pollution. To address this, an organic waste management program was implemented with the involvement of students and teachers. The methods used include observation, interviews, socialization, sorting training, and composting. Waste is processed in used plastic containers, which also serve as containers for growing school medicinal plants (TOS). The results of the activities show an increase in students' environmental awareness, as well as the creation of a simple waste management system and opportunities for creative economic activities. This program also supports skill-based learning and the role of students as agents of change. Despite facility constraints, it has had a positive impact on the environment, society, and education, while consistently applying the 3R principles (Reduce, Reuse, Recycle).